Using Center of Islamic Business and Economic Studies Model (CIBEST Model) to Measure Islamic Poor of Indeks in Pekanbaru City 2014-2016 - Emkhad Arif (UIR Press, 2016)
This study aims to measure and assess the level of poverty and the welfare of citizen in Pekanbaru. The difference of this research with other research lies in how to measure poverty and social welfare Pekanbaru city that does not use indicators of the level of income and consumption, but to measure and assess the degree to Pekanbaru city public welfare by using CIBEST Model. Formulation of the problem in this study is not yet known the level of welfare of Pekanbaru when measured by using analytical tools CIBEST MODEL. This study focuses on measuring the level of welfare of Pekanbaru by using analytical tools CIBEST MODEL. The research method in this study is a quantitative research methods. Samples in this study are families (KK ) who live in the district ofBukit Raya and Marpoyan Damai.The results of this study show, score SH respondents, shows the average value over three (3). SH value reflects the spiritual values ​​of a family. So we can conclude the value of spirituality of households who responded are in quadrant 1, which is prosperous, while the value of MV which illustrates the level of the minimum requirements that must be met by a family in a position above the standard poverty line (GK), thus showing that it materill heads of family in Pekanbaru also are in quadrant 1, which is prosperous. So overall if analyzed using MODEL CIBEST it can be concluded that the majority of households/families in the city of Pekanbaru is in quadrant 1 depicting well-being, both non- material well-being (religion) and material (clothing, food and shelter).